Hubungan Karakteristik Suami dengan Tingkat Pengetahuan Suami tentang Pijat Oksitosin di PMB Turasmiyati Kota Bekasi - Rinasari Marliaty; Siti Julaila (Pusat Riset dan Inovasi Nasional, 2023)
The coverage of exclusive breastfeeding in Indonesia has not reached 80%. One of the causes of low breastfeeding coverage is the support of the closest people, especially the husband's knowledge. Efforts that can be made to provide smooth breastfeeding for postpartum mothers include oxytocin massage performed by health workers and husbands. The type of research used is an analytical type of research, namely a study that involves data collection activities to determine whether there is a relationship between two or more variables. This study uses a cross-sectional approach by conducting observations or data collection. Of the 30 respondents, the husband's knowledge at TPMB Turasmiyati, most of them have good knowledge of oxytocin massage. There is a relationship between husband's knowledge of oxytocin massage and age, there is a significant relationship between husband's knowledge of oxytocin massage and education, but there is no significant relationship between level of knowledge and work. It is recommended to all related parties, both health workers and family members, to work together so that exclusive breastfeeding can be fulfilled.